Australian councils unelected by the citizens in an Indigenous setting: The case of Nhulunbuy in the Northern Territory - Pearson, Cecil (Blackwell Publishing Asia P/L, 2012)
Within the Australian democratic nation there are towns where the citizens are governed by administrations that have not been democratically elected by the residents. These unique residential centres are termed ‘special purpose towns’ that can be transformed to a permanent community governed by a democratic structure through a process termed normalisation. This paper examines the special purpose mining town of Nhulunbuy in the Northern Territory of Australia, which is on the cusp of the normalisation process. The paper outlines the similarities and differences of local government roles and responsibilities with Australian towns or shires that have publicly elected executive members. How Indigenous people are facilitating the normalisation of Nhulunbuy, through cultural perceptions of opportunity, is discussed. A concluding focus challenges well established conventional frameworks endorsing the roles of governments and miners in the normalisation phenomenon.